Implementasi Algoritma Needleman-Wunsch dalam Pengujian Tingkat Kemiripan DNA Babi Sulawesi Utara - Ngovangari, Rivchi Hanni; Rorimpandey, Gladly Caren; Kembuan, Olivia; Sumual, Hendro Maxwell (JOINTER : Journal of Informatics Engineering, 2024)
Data is a collection generated from various media used by humans. DNA data is a form of data, which is data in the form of genetic code text to store biological identities and characteristics of living things. This study used DNA to test the similarity level of North Sulawesi pigs. The method used is the Pairwise Sequence Alignment method. With sequences of different DNA lengths, the researcher implemented the Needleman-Wunsch algorithm for alignment. Matching is used using the BioPython module, which is in pairwise2. And this study produces a model and proportion of the similarity level of North Sulawesi Pigs that can be used as future references for biological research on molecular biology or for the field of informatics in implementing Needleman-Wunsch algorithm in Python, or references and additional knowledge for research in Bioinformatics.